Combined Parietal-Insular-Striatal Cortex Stroke with New-Onset Hallucinations: Supporting the Salience Network Model of Schizophrenia. (24th January 2020) - Nanda, Saheba; Priya, Krishna; Khan, Tasmia; Patel, Puja; Azizi, Heela; Nuthalapati, Deepa; Paul, Christen; Sippy, Rabina; Simsam, Abdulkader Hmidan; Abraham, Jesslin; Singh, Gurjinder; Goodarzi, Alireza; et al.
Abstract : Brain imaging studies have identified multiple neuronal networks and circuits in the brain with altered functioning in patients with schizophrenia. These include the hippocampo-cerebello-cortical circuit, the prefrontal-thalamic-cerebellar circuit, functional integration in the bilateral caudate nucleus, and the salience network consisting of the insular cortex, parietal anterior cingulate cortex, and striatum, as well as limbic structures. Attributing psychotic symptoms to any of these networks in schizophrenia is confounded by the disruption of these networks in schizophrenic patients. Such attribution can be done with isolated dysfunction in any of these networks with concurrent psychotic symptoms. We present the case of a patient who presents with new-onset hallucinations and a stroke in brain regions similar to the salience network (insular cortex, parietal cortex, and striatum). The implication of these findings in isolating psychotic symptoms of the salience network is discussed.